2017
DOI: 10.1002/ijgo.12083
|View full text |Cite
|
Sign up to set email alerts
|

Sexual activity among Nigerian women following successful obstetric fistula repair

Abstract: Following obstetric fistula repair, many women experienced difficulty engaging in penetrative vaginal intercourse and reported sexual dysfunction. Management of sexual dysfunction should be part of fistula rehabilitation programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Studies assessing patient-focused outcomes of surgery have identified significant short-term improvements including enhanced overall quality of life [21], psychological status [22], social functioning [23,24] and economic status [25]. However, they also report significant long-term challenges, including persistent residual incontinence [20,26,27], pain and weakness [21,28], and sexual and fertility complications [5,21,[29][30][31]. Lingering physical problems such as these reduce women's ability to resume social roles, making them less likely to consider themselves to have recovered [3, 21, 25, 32,] and placing them at greater risk of continued poor mental health [28,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Studies assessing patient-focused outcomes of surgery have identified significant short-term improvements including enhanced overall quality of life [21], psychological status [22], social functioning [23,24] and economic status [25]. However, they also report significant long-term challenges, including persistent residual incontinence [20,26,27], pain and weakness [21,28], and sexual and fertility complications [5,21,[29][30][31]. Lingering physical problems such as these reduce women's ability to resume social roles, making them less likely to consider themselves to have recovered [3, 21, 25, 32,] and placing them at greater risk of continued poor mental health [28,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Sexuality is an important component of women's overall well-being, with quality of life and sexual dysfunction contributing to personal and interpersonal stress; this could be especially important for women with genital tract injuries from either obstetric trauma or surgical interventions as one of the major causes of rectovaginal fistula [34]. Given that patient mental health and social functioning appear to improve following surgical fistula repair, it is essential for patients to be referred for surgery in a timely manner following obstructed labor [13].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they avoid risky behaviours including sexual intercourse and childbirth subsequently resulting in marital conflicts. 15,16 Accordingly, they fear penetrative intercourse due to a narrowed vagina. 16 Their opportunities for earning a living are also minimal.…”
Section: Challenges To the Rehabilitation Of Obstetric Fistula Patientsmentioning
confidence: 99%
“…15,16 Accordingly, they fear penetrative intercourse due to a narrowed vagina. 16 Their opportunities for earning a living are also minimal. 8,17,18 Such challenges are not unique to Sub-Saharan countries but also in South Asia.…”
Section: Challenges To the Rehabilitation Of Obstetric Fistula Patientsmentioning
confidence: 99%
See 1 more Smart Citation